Individual Communications Against Poland Before the Human Rights Committee: a Review and Tentative Conclusions - Łasak, Katarzyna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2017)
Poland has been a party to the International Covenant on Civil and Political Rights of 16 December 1966 for forty years, and has been recognizing the right of individuals to submit applications to the Human Rights Committee for 25 years. The total number of communications amounts to 11, and the results of the examination thereof encourage consideration of denouncing the Optional Protocol to the International Covenant on Civil and Political Rights of 16 December 1966.